Crop plans based on frequencies of dry and wet spells at Daringibadi block of Kandhamal district - PARDHAN, P C; SENAPATI, P C; SUBUDHI, C R (The Indian Journal of Agricultural Sciences, 2013)
An investigation was conducted during 1996 for agricultural management and planning of Daringbadi block ofKandhamal district which comprised 70% tribal and scheduled caste population. Markov chain model has been appliedto know the probability of having different condition, dry and wet pentads (5 consecutive days) and also forward andbackward accumulation of rain water suitable for crop production. The analysis showed that 2 short duration crops canbe raised in a year, one in rainy season (kharif) and the other in winter season (rabi). A number of cropping systemsincluding intercropping and sequence cropping have been proposed based on the wealth condition of the region.